Synthesis of alumina/YAG 20 vol% composite by co-precipitation - Radosław Lach; Krzysztof Haberko; Mirosław Bućko (Processing and Application of Ceramics, 2011)
Co-precipitation of alumina/YAG precursor from aluminum and yttrium nitrate solution with ammonium carbonate results in dawsonite. Its crystallographic parameters differ from the compound precipitated with no yttrium additive. It suggests that yttrium ions become incorporated into the dawsonite structure. The DSC/TG and X-ray diffraction measurements show decomposition of dawsonite at elevated temperatures resulting in γ-Al2O3 and then δ- and θ-alumina modifications. Full transformation to α-Al2O3 and YAG occurs at temperatures higher than 1230°C. Starting powder for the sintering experiments was prepared using the coprecipitated precursor calcined at 600°C. Seeding of such powder with 5 wt.% α-Al2O3 results in material of 98% density at 1500°C. Much lower densification show compacts of unseeded powder.